2021
DOI: 10.1016/j.brainres.2021.147331
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a 30-day spaceflight on the structure of motoneurons of the trochlear nerve nucleus in mice

Abstract: During spaceflight and immediately after it, adaptive neuroplastic changes occur in the sensorimotor structures of the central nervous system, which are associated with changes of mainly vestibular and visual signals. It is known that the movement of the eyeball in the vertical direction is carried out by muscles that are innervated by the trochlear nerve (CN IV) and the oculomotor nerve (CN III). To elucidate the cellular processes underlying the atypical vertical nystagmus that occurs under microgravity cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Experiments examining changes in mouse brain tissue in actual cosmic space have reported increased dendritic spines of motoneurons, increased number and size of axonal mitochondria, changes in synaptic morphology, and increased synaptic transmission. 23,24 Experiments analyzing changes in bMSCs exposed to an MG environment by spaceflight showed downregulation of cytoskeletal genes and cytoskeleton changes, suggesting that the expression of genes involved in neurogenesis is altered, promoting the activation of neurogenic processes such as nervous system development, differentiating neuron morphogenesis, and increased synaptic transmission. 9,26 Regarding the effect of MG environment on the cytoskeleton, Ulbrich et al and Doty et al reported a decrease in extracellular matrix production in culture experiments with bone and cartilage cells and tumor cells under MG. 27,28 In a parabolic flight experiment, the cytoskeletal systems such as actin and cytokeratin exposed to an MG environment were found to be altered and cells were observed to leave their adherent state, resulting in gene expression changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments examining changes in mouse brain tissue in actual cosmic space have reported increased dendritic spines of motoneurons, increased number and size of axonal mitochondria, changes in synaptic morphology, and increased synaptic transmission. 23,24 Experiments analyzing changes in bMSCs exposed to an MG environment by spaceflight showed downregulation of cytoskeletal genes and cytoskeleton changes, suggesting that the expression of genes involved in neurogenesis is altered, promoting the activation of neurogenic processes such as nervous system development, differentiating neuron morphogenesis, and increased synaptic transmission. 9,26 Regarding the effect of MG environment on the cytoskeleton, Ulbrich et al and Doty et al reported a decrease in extracellular matrix production in culture experiments with bone and cartilage cells and tumor cells under MG. 27,28 In a parabolic flight experiment, the cytoskeletal systems such as actin and cytokeratin exposed to an MG environment were found to be altered and cells were observed to leave their adherent state, resulting in gene expression changes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many experiments have been conducted in space, suggesting that an MG environment is a useful tool for cell culture in cell therapy. 9,10,23,24 However, since experiments in space are highly expensive, we used "Gravite," a multi-directional gravity control device developed by our group, to simulate MG. 1,11,25 In vitro experiments showed that genes related to cell proliferation, angiogenesis, neurotrophy, anti-apoptosis, nerve and synapse organization, and cell differentiation inhibition were significantly upregulated in the miRNA-MG group than in the miRNA-1G group. In contrast, genes promoting microtubule and extracellular matrix formation, cell adhesion, cell signaling, and cell differentiation were significantly downregulated in the miRNA-MG group compared with the miRNA-1G group.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Mikheeva et al reported that after 30 days flight on the Bion-M1 biosatellite, the number and size of mitochondria in the soma of motoneurons and in axons coming from the vestibular structures increased in mouse [ 22 ]. Tan et al showed that when compared with cells maintained under normal gravity, BL6-10 cells treated with simulating microgravity showed higher mitochondrial content and more abundant cytoplasmic mitochondria, and significantly reduced glycolytic metabolism [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…During long-term space operations 61 , microgravity may affect intracranial physiological functions, such as intracranial pressure, spinal and neurocognitive performance, and brain edema induced by microgravity 92 , resulting in neuro-ocular syndrome 62 . Irina Mikheeva et.al observed 93 that 30-day space ight had a signi cant effect on the structure of motoneurons of the trochlear nerve nucleus in mice. Xiao Wen Mao et.al found that the mice exposure to the space ight environment (Space Shuttle Atlantis, STS-135, 13 day) could induce signi cant changes in protein expression related to neuronal structure and metabolic function.…”
Section: Discussionmentioning
confidence: 99%